Treinamento funcional altera o perfil metabólico, mitocondrial e redox de células mononucleares de mulheres com síndrome metabólica - Rosa, Pamela Carvalho da (2019)
Metabolic syndrome (MS) is a combination of metabolic abnormalities, such as hypertension, hyperglycemia, abdominal obesityand dyslipidemia. These conditions occur simultaneously and increase the risk for type 2 diabetes and cardiovascular diseases development, and may be related to mitochondrial and antioxidant defense system dysfunction, once those conditions increase reactive oxygen species (ROS) generation, reduction of oxidative phosphorylation and, consequently, lower ATP synthesis. In this sense, the development of therapeutic strategies, including lifestyle interventions, such as diet and regular physical exercises directed to mitochondria metabolism, might be relevant and important for MS treatment and prevention. Moreover, it is well-known the beneficial effects of exercise at mitochondrial metabolism and redox states, but its impact on peripheral blood mononuclear cells (PBMCs) from patients with MS remains unclear. Therefore, this study intends to determine whether exercise training changes the energy metabolism, mitochondrial complexes capability and oxidative stress th MS, and associate them to the exercise parameters. To this, untrained middle-age women over 45 years old, and with three risk factors related to MS were recruited. Participants performed a functional training protocol during the 12-weeks (3d/wk). Cells (PBMCs) were obtained from subject's blood collection with MS before training (baseline) and 72 hours after the end of the training protocol (to avoid acute exercise effects - after training). After isolation, PBMCs were used to measure the following parameters: lactate dehydrogenase (LDH) and citrate synthase (CS) activity related for energy metabolism, and the mitochondrial complexes respiratory capability (I-IV). ROS production was performed for dichlorofluorescein oxidation and hydrogen peroxide (H2O2) production, as well as catalase (CAT) activity associated endogenous antioxidant system. The training protocol produced an increase in PBMCs LDH levels, while CS activity remained unaltered. Moreover, PBMCs demonstrated an increase in exercise-induced ROS formation, as well as antioxidant system improvement, indicating an adaptation mechanism. The PBMCs depicted an increase in dehydrogenases activity and mitochondrial electron transfer capacity. Moreover, had an increase aerobic capacity in participants, while body weight remained unaltered after training. In conclusion, we provided novel evidence that a 12-week functional exercise-training program modifies PBMCs redox state and mitochondrial electron transfer capacity in response to metabolism stimulation, in addition to improved aerobic capacity in women with MS. Therefore, our data suggests that PBMCs could be effective to detect and assess changes cellular profiles from unhealthy patients, as well as biomarkers source for physical exercise control and quality.